Shelf life extension of pasteurized coconut milk using chitosan as a natural preservative - Boonmeesuk , Woraphon; Praniti , Siramon; Chuesiang, Piyanan; Ryu , Victor; Siripatrawan , Ubonrat (Asia-Pacific Journal of Science and Technology, 2024)
This research aimed to seek a natural food preservative by applying chitosan to preserve quality and extend the shelf life of pasteurized coconut milk. Coconut milk containing different concentrations of chitosan (0, 1, 3, and 5%(v/v)) were pasteurized at 72°C for 20 min and stored at 4°C. The changes in fatty acid (FFA), peroxide value (PV), pH, colors, total viable count (TVC), and sensory quality were monitored throughout the storage time. The shelf life was then evaluated using an accelerated shelf life test. The pasteurized coconut milk added with chitosan had lower FFA content, PV, TVC, and degree of phase separation than that without chitosan. These results indicated the ability of chitosan to retard lipolysis and lipid oxidation, inhibit microbial growth, and improve the stability of pasteurized coconut milk. Pasteurized coconut milk with 3% chitosan received the highest sensory scores, and thus its shelf life was further investigated using the temperature quotient (Q10) technique. Pasteurized coconut milk with 3% chitosan had a longer shelf life (7 days) than the control (2 days). Overall, chitosan can be used as a natural preservative to delay changes in the chemical, physical and biological quality of pasteurized coconut milk, while it did not show a negative effect on the coconut milk’s organoleptic quality. The opportunity of using chitosan as a natural food preservative is achievable.